2022
DOI: 10.1530/erc-22-0218
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic disorders in patients with pheochromocytomas and sympathetic paragangliomas

Abstract: The objective of our study was to determine de prevalence of glycemic disorders (diabetes mellitus and prediabetes) in patients with pheochromocytomas and sympathetic paragangliomas (PPGLs) and identify risk factors for their development and the likelihood of their resolution after surgery. A multicentric retrospective study of patients with PPGLs submitted to surgery between 2000-2021 in seventeen Spanish hospitals was performed. Diabetes-specific data were collected at diagnosis, in the immediate and long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Glycemic disturbances in patients with pheochromocytoma have been a subject of study in the last few years. We observed glucose alterations in 40% of our patients, which corresponds well to the published data [25,26]. These alterations may be related to the catecholamine-induced insulin resistance or insulin suppression.…”
Section: Discussionsupporting
confidence: 91%
“…Glycemic disturbances in patients with pheochromocytoma have been a subject of study in the last few years. We observed glucose alterations in 40% of our patients, which corresponds well to the published data [25,26]. These alterations may be related to the catecholamine-induced insulin resistance or insulin suppression.…”
Section: Discussionsupporting
confidence: 91%
“…[65,69,70] In contrast, another study reported no difference between BAT-activated and non-activated groups, although the study included patients with nonsecretory PPGL without BAT activation. [63] In a study investigating BAT gene expression in patients with PPGL, the mRNA levels of related genes were positively correlated with catecholamine [44] 229 23.6 Sporadic PPGL; hypertension 51.9 56.8 mo 2023 Zhao L [43] 163 metabolites and decreased with age and BMI, consistent with the general population. [61] These studies suggest that the high concentration of circulating catecholamines in patients with PPGL leads to excessive sympathetic nervous system activation and subsequently triggers BAT activation, rather than the disease itself.…”
Section: Bat Contributions To Hypermetabolismmentioning
confidence: 71%
“…This might be due to adrenaline's high affinity for α2 receptors to stimulate pancreatic β-cells, leading to reduced insulin secretion, and noradrenaline's high affinity for α1 and β3 receptors to stimulate pancreatic α-cells and adipocytes, leading to increased glucagon and free fatty acids (FFAs) levels, thus increasing hepatic glycogen synthesis and breakdown. [40] Recent studies indicate that the risk factors for preoperative glucose abnormalities include older age, [37,[41][42][43] hypertension comorbidity, [42][43][44] symptomatic tumors, [42,45,46] longer disease duration, [37] larger tumor size, [42] 24-hour urinary norepinephrine [37,43] or epinephrine levels, [43] and sporadic PPGL [44] (Table 2). Additionally, following tumor removal, many patients with PPGL experience recovery or partial relief of impaired glucose tolerance.…”
Section: Catecholamines Enhance Substance Metabolism In Patients With...mentioning
confidence: 99%